2020
DOI: 10.34117/bjdv6n3-216
|View full text |Cite
|
Sign up to set email alerts
|

Marcha de absorção de nutrientes em meloeiro ‘goldex’ fertirrigado

Abstract: RESUMONo presente trabalho objetivou-se determinar a marcha de acumulação de macro e de micronutrientes cultivado sob fertirrigação. O experimento foi realizado em área pertencente à Empresa Ecofértil Brazilian Journal of DevelopmentBraz. 12655Agropecuária LTDA localizada no município de Aracati (CE). O experimento foi instalado em delineamento de blocos casualizados com 9 tratamentos, correspondentes a 9 períodos de avaliação 14, 21, 28, 35, 42, 49, 56, 63, 70 dias após transplantio com quatro repetições. Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…After drying, the material was weighed and crushed in a Willey mill for sulfur digestion according to the methodology described by Carmo et al (2000) to determine the contents of N, P, K, Ca, Mg, Fe, Mn, Zn, Regarding the distribution of dry matter in each organ of the plant, the fruits showed the greatest increase in quantity, followed by the leaves and stems with lower values. This is similar to the findings of Oliveira (2017), wherein the fruit stood out in the accumulation of dry matter compared to the vegetative part (leaf + stem).…”
Section: Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…After drying, the material was weighed and crushed in a Willey mill for sulfur digestion according to the methodology described by Carmo et al (2000) to determine the contents of N, P, K, Ca, Mg, Fe, Mn, Zn, Regarding the distribution of dry matter in each organ of the plant, the fruits showed the greatest increase in quantity, followed by the leaves and stems with lower values. This is similar to the findings of Oliveira (2017), wherein the fruit stood out in the accumulation of dry matter compared to the vegetative part (leaf + stem).…”
Section: Methodssupporting
confidence: 88%
“…However, the fruits only accumulated 264.33 g (0.58 lb) ha -1 at the 64 th DAE, which was 20% of the total Fe, in contrast to the findings of Melo et al (2013), where the fruits at 70 days after transplanting obtained a value of 8.48 mg plant -1 (141.33 g or 0.31 lb ha -1 ). Moreover, concerning the total Fe accumulated by the 'Gladial®' melon, it was observed that this occurred linearly and that this micronutrient had a slow accumulation until 14 DAE and intensified after 21 days, which was also noted by Oliveira (2017).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation